1976
DOI: 10.1017/s0027763000024715
|View full text |Cite
|
Sign up to set email alerts
|

On classification of quasi-symmetric domains

Abstract: The notion of "Siegel domains" was introduced by . It was then shown that every homogeneous bounded domain is holomorphically equivalent to a Siegel domain (of the second kind) determined uniquely up to an affine isomorphism ([15] . The purpose of the present note is to show that this classification can also be obtained immediately from my previous result on linear imbeddings of self-dual cones ([10a]).Our method is based on the following two observations: (I) There are natural equivalences between the three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Using the theory of representations of Jordan algebras [24] and the theory of Clifford algebras [2], [8] it is possible to find an explicite description of all quasisymmetric Siegel domains. This in particular reproduces results of I. Satake [46], [47], [48], and M. Takeuchi [53]. Moreover, a Cayley transformation for quasisymmetric Siegel domains and the symmetries of a symmetric Siegel domain can be stated explicitly.…”
supporting
confidence: 85%
“…Using the theory of representations of Jordan algebras [24] and the theory of Clifford algebras [2], [8] it is possible to find an explicite description of all quasisymmetric Siegel domains. This in particular reproduces results of I. Satake [46], [47], [48], and M. Takeuchi [53]. Moreover, a Cayley transformation for quasisymmetric Siegel domains and the symmetries of a symmetric Siegel domain can be stated explicitly.…”
supporting
confidence: 85%
“…REMARK. A classification of the symmetric Siegel domains has been obtained by different methods in [13], [14], [15].…”
Section: Iqss Have Been Classified By Different Methods Inmentioning
confidence: 99%
“…The notion of a quasisymmetric domain was originally defined by Satake [13]; Dorfmeister [9] showed that this was equivalent to the condition that be a Jordan algebra. D'Atri and Miatello [6] proved that an irreducible domain is quasisymmetric if and only if there are constants a and b so that dim n(l/2)(ek+em) : b, 1 ~< k < m ~< r, and dim n(1/2)t k ----a, 1 ~< k ~< r.…”
Section: An Irreducible Homogeneous Siegel Domain Is Quasisymmetric Imentioning
confidence: 99%
See 1 more Smart Citation
“…Here we refine this result and prove that the holomorphic sectional curvature is bounded above by a negative constant. (see [4]). (see [4]).…”
Section: Proceedings Of the American Mathematical Societymentioning
confidence: 96%